Residual stress modeling in minimum quantity lubrication grinding. Issue 5 (March 2016) - Shao, Yamin; Fergani, Omar; Li, Beizhi; Liang, Steven
Abstract Minimum quantity lubrication (MQL) has been proposed as a promising alternative to conventional flood cooling to substantially reduce the lubrication usage while maintaining high surface quality. Residual stress induced by grinding process directly affects the surface quality of the final product. An analytical relationship between residual stresses and process conditions such as process parameters, material properties, and lubrication conditions could support process planning and optimization of MQL grinding. This paper has presented a physics-based model to predict residual stresses in grinding with consideration of the lubrication and cooling effects of MQL. Grinding force and temperature distribution in the workpiece are used to calculate the loading stresses imparted by MQL grinding. The loading stresses are then coupled into a rolling/sliding contact algorithm to solve for residual stresses. Experimental measurements of residual stress profile under and flood cooling conditions have been pursued to calibrate and validate the predicted results.